PEMIKIRAN ABDURRAHMAN WAHID TENTANG TOLERANSI BERAGAMA - Swardiyamsyah Swardiyamsyah (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The idea of tolerance Abdurrahman Wahid is the subject of study in this study, is a reflection on the process of dialogue became a Muslim and a true citizen. This research is a documentary research that uses methods of critical analysis. The main data used in this thesis is related to the theme of the books in question, either written by themselves and others who write about Abdurrahman Wahid. Theoretical base that is used to analyze the theory of tolerance. There are two conclusions derived from the analysis of the data in this study; first, thinking Abdurrahman Wahid of tolerance is more focused on how the attitudes and actions of individuals in interaction in a pluralistic society is religious, he considers that tolerance is a necessity in the life of a cosmopolitan that tolerance should be owned by those who want the order of life be calm, and peaceful because tolerance is respect, this basis begins with the acceptance of pluralism in acting and thinking. Second, the influence of the ideas Abdurrahman Wahid gave a very significant impact on the lives of religion, nation and state, it can be seen from the successes of Abdurrahman Wahid completed several real issue is very sensitive, such as the handling of terrorism cases, the Ahmadiyah case is addressed in a lighter, freedom of the Tionghioa with the launch of Confucian Religion, Religious Pluralism rapidly growing and its influence in the world of practical politics and the state.Keyword: Thought, Abdurrahman Wahid, religious tolerance